The physiology and biochemistry of prokaryotes - White, David, 1936- (Oxford University Press, 2007)
The third edition of The Physiology and Biochemistry of Prokaryotes covers the basic principles of prokaryotic physiology, biochemistry, and cell behavior. It presents microbial metabolism in the context of the chemical and physical problems that cells must solve in order to grow.